Geoformas asociadas al batolito antioqueño (1998)
The Antioquian Batholith is the biggest plutonic body in the Central Cordillera of Colombia. It intrudes all the surrounding rocks, and differs from other plutonic bodies from orogenic chains by its lithological homogeneity and low petrochemical variations; its most important facies are the granodioritetonalite series: massive, phaneritic, equigranular and medium grained rocks.  The humid ecuatorial climate of Colombian Andes favors chemical weathering of the Antioquian Batholith,  and has produced a thick saprolith cover.  The trapezoid shape of the Antioquian Batholith and the deformation associated with its emplacement  have not been entirely explained yet; on the eastern edge shear zones occur where weathering and erosion processes take place and accelerate the development of particular geoforms such as quartz blocks and tablular forms.  The geoforms are the result of geological processes and the climatic conditions that had affected the batolithit since it reached the surface. The morphologic evolution depends on several phenomena such as chemical weathering, and the transport and erosive agents that modify the landscape.  Characteristic geoforms developed on the Antioquian Batolith are: "pefioles", boulders, "organ ales", "acanaladuras", quartz lines, tabular forms and pseudokarst, and several erosion surfaces generated by the uplift of the Central Cordillera and separated by deep valleys.